Decoding Millennial Financial Behavior: Factors Shaping Financial Management Nexus: Membongkar Nexus Keuangan: Eksplorasi Faktor yang Membentuk Perilaku Pengelolaan Keuangan Generasi Milenial - Nesia Odila; Wisnu Panggah Setiyono (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the influence of Financial Literacy, Financial Knowledge, Financial Attitude, Locus of Control, and Income on Financial Management Behavior among millennials in Sidoarjo City. Recognizing the prevalent lack of financial knowledge in this generation, we emphasize the pivotal role of individual financial conditions in fostering effective financial management for the future. Employing a quantitative approach, we collected data through questionnaires distributed to 100 respondents. The analysis was conducted using multiple linear regression with the PLS (Partial Least Squares) program. The findings reveal that Financial Literacy, Financial Knowledge, Financial Attitude, Locus of Control, and Income significantly affect Financial Management Behavior. Furthermore, the simultaneous impact of these factors on millennials' financial behavior is evident. This study sheds light on the complex interplay between various elements and provides valuable implications for financial education programs, policymakers, and individuals seeking to enhance their financial well-being in the ever-evolving financial landscape. Highlights: Financial Literacy: Understanding the impact of financial literacy on the financial management behavior of millennials in Sidoarjo City. Factors Influencing Behavior: Exploring the significant factors such as financial knowledge, attitude, locus of control, and income that shape the financial management behavior of millennials. Implications for Financial Education: Providing valuable insights for financial education programs, policymakers, and individuals to enhance financial well-being among the millennial generation. Keywords: Financial Literacy, Millennial Generation, Financial Management Behavior, Financial Knowledge, Locus of Control